2008
DOI: 10.1590/s1516-89132008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and analysis of the mitochondrial DNA control region in the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae)

Abstract: This study aimed at the sequence and analysis of the mtDNA control region (CR) of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The rrn L transcript was also present in the highest proportion of D. melanogaster [11] and porcine cistrons [10] , and the analogous large abundance of rrnL transcripts in human expression data was attributed to the presence of a second HSP upstream of the gene that terminates in proximity near the tRNA LeuUUR downstream of the 16 S rRNA [66] , [67] , [68] . The HSP and LSP sequences have diverged rapidly in mammalian systems [69] , such that defining these functional regions is difficult by comparative sequence analyses [70] . The proportional range of cistron levels for those that encode for proteins involved in the same process showed ≤11.15-fold difference in cistron quantities for the NADH dehydrogenase complex ( nd 1 vs. nd 2), and a ≤3.59-fold variance among cistrons for the cytochrome c oxidase ( cox II vs. cox III).…”
Section: Resultsmentioning
confidence: 99%
“…The rrn L transcript was also present in the highest proportion of D. melanogaster [11] and porcine cistrons [10] , and the analogous large abundance of rrnL transcripts in human expression data was attributed to the presence of a second HSP upstream of the gene that terminates in proximity near the tRNA LeuUUR downstream of the 16 S rRNA [66] , [67] , [68] . The HSP and LSP sequences have diverged rapidly in mammalian systems [69] , such that defining these functional regions is difficult by comparative sequence analyses [70] . The proportional range of cistron levels for those that encode for proteins involved in the same process showed ≤11.15-fold difference in cistron quantities for the NADH dehydrogenase complex ( nd 1 vs. nd 2), and a ≤3.59-fold variance among cistrons for the cytochrome c oxidase ( cox II vs. cox III).…”
Section: Resultsmentioning
confidence: 99%
“…The mtDNA control region and ITS have been successfully employed as molecular markers in some studies of population genetic structure (Vandewoestijne et al 2004;Kim et al 2007;Bravo et al 2008;Depaquit et al 2008;Meraner et al 2008;Hamarsheh et al 2009). In this study, we employed the mtDNA A?T-rich region and nuclear ITS2 sequence in order to evaluate, for the first time, the genetic diversity and geographic variations of S. litura.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group recently described the Diatraea saccharalis mitochondrial control region, CR (Bravo et al, 2008). Sequence analysis demonstrated that this region of the D. saccharalis mitochondrial genome has high similarity with that of the Lepidopteran Cydia pomonella; however, these results did not clarify the taxonomic problem posed by D. saccharalis.…”
Section: Diatraea Saccharalis Barcodementioning
confidence: 94%